CircARVCF Contributes to Cisplatin Resistance in Gastric Cancer by Altering miR-1205 and FGFR1 - Zhang, Ruirui; Zhao, Huanyu; Yuan, Hongmei; Wu, Jian; Liu, Haiyan; Sun, Suan; Zhang, Zhengwei; Wang, Jiayang (Frontiers in Genetics, 2021)
Background: Chemoresistance is a major barrier to the treatment of human cancers. Circular RNAs (circRNAs) are implicated in drug resistance in cancers, including gastric cancer (GC). In this study, we aimed to explore the functions of circRNA Armadillo Repeat gene deleted in Velo-Cardio-Facial syndrome (circARVCF) in cisplatin (DDP) resistance in GC. Methods: The expression of circARVCF, microRNA-1205 (miR-1205) and fibroblast growth factor receptor 1 (FGFR1) was detected by quantitative real-time polymerase chain reaction (qRT-PCR), western blot assay or immunohistochemistry (IHC) assay. Cell Counting Kit-8 (CCK-8) assay and colony formation assay were performed to evaluate DDP resistance and cell colony formation ability. Transwell assay was conducted to assess cell migration and invasion. Flow cytometry analysis was done to analyze cell apoptosis. Dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay were manipulated to analyze the relationships of circARVCF, miR-1205 and FGFR1. Murine xenograft model was constructed to explore DDP resistance in vivo. Results: CircARVCF level was increased in DDP-resistant GC tissues and cells. CircARVCF silencing inhibited DDP resistance, colony formation and metastasis and induced apoptosis in DDP-resistant GC cells. CircARVCF directly interacted with miR-1205 and miR-1205 inhibition reversed circARVCF silencing-mediated effect on DDP resistance in DDP-resistant GC cells. FGFR1 served as the target gene of miR-1205. MiR-1205 overexpression restrained the resistance of DDP-resistant GC cells to DDP, but FGFR1 elevation abated the effect. In addition, circARVCF knockdown repressed DDP resistance in vivo. Conclusion: CircARVCF enhanced DDP resistance in GC by elevating FGFR1 through sponging miR-1205.